4h-14hj+16hj+13hj+15hj-17hj=

Simple and best practice solution for 4h-14hj+16hj+13hj+15hj-17hj= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4h-14hj+16hj+13hj+15hj-17hj= equation:


Simplifying
4h + -14hj + 16hj + 13hj + 15hj + -17hj = 0

Combine like terms: -14hj + 16hj = 2hj
4h + 2hj + 13hj + 15hj + -17hj = 0

Combine like terms: 2hj + 13hj = 15hj
4h + 15hj + 15hj + -17hj = 0

Combine like terms: 15hj + 15hj = 30hj
4h + 30hj + -17hj = 0

Combine like terms: 30hj + -17hj = 13hj
4h + 13hj = 0

Solving
4h + 13hj = 0

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Factor out the Greatest Common Factor (GCF), 'h'.
h(4 + 13j) = 0

Subproblem 1

Set the factor 'h' equal to zero and attempt to solve: Simplifying h = 0 Solving h = 0 Move all terms containing h to the left, all other terms to the right. Simplifying h = 0

Subproblem 2

Set the factor '(4 + 13j)' equal to zero and attempt to solve: Simplifying 4 + 13j = 0 Solving 4 + 13j = 0 Move all terms containing h to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 13j = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 13j = 0 + -4 13j = 0 + -4 Combine like terms: 0 + -4 = -4 13j = -4 Add '-13j' to each side of the equation. 13j + -13j = -4 + -13j Combine like terms: 13j + -13j = 0 0 = -4 + -13j Simplifying 0 = -4 + -13j The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Solution

h = {0}

See similar equations:

| 5x+5(3x-31)=-355 | | 5x^4+3x+7=0 | | 135+x+80=180 | | 12-5t=2 | | 5t+3+2t-6t=1+2 | | 5x+5(x-31)=-355 | | 32=2(l+w) | | 16=208 | | 4p-7=19 | | 2[k-(3k+12)+6]=2(k+6) | | 144+x+5= | | z=ln(x-7y) | | -2t-5t=2 | | x(9x+3)=0 | | 5x+2y=-27 | | (-71+2y)-2y=-13 | | 13=0.25X+6 | | X(3x-6)=99 | | -3v-21=7-(7v+8) | | 12-4(2w-3)=7-(3-4w) | | 0.08x+(2160-0.18x)=15000 | | -0.1m+12=67 | | 3x+5x=7x-9 | | 5(1-m)-2(1-m)=15 | | 23=6y+11 | | 2(7s+6)-5s=3(3s+6)-20 | | 16x^2+48x-36=0 | | 42+105+x=180 | | 4x+5x-3x=120 | | -6+n+2= | | 5.7x+5=4.7x | | 0.5c+7.3=29.3 |

Equations solver categories